2013
DOI: 10.1590/0037-8682-0054-2012
|View full text |Cite
|
Sign up to set email alerts
|

cagE as a biomarker of the pathogenicity of Helicobacter pylori

Abstract: Introduction:Helicobacter pylori infection is associated with gastro-duodenal diseases. Genes related to pathogenicity have been described for H. pylori and some of them appear to be associated with more severe clinical outcomes of the infection. The present study investigates the role of cagE as a pathogenicity biomarker of H. pylori compare it to cagA, vacA, iceA and babA2 genes and correlate with endoscopic diagnoses. Methods: Were collected biopsy samples of 144 dyspeptic patients at the Hospital of the Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…We have read with interest the article entitled "cagE as a biomarker of the pathogenicity of Helicobacter pylori" by Ramis et al 1 . In this study, with a sample size of 57, the authors suggested that cagE is an important prognostic indicator for developing lesions during Helicobacter pylori infection.…”
Section: Dear Editormentioning
confidence: 99%
“…We have read with interest the article entitled "cagE as a biomarker of the pathogenicity of Helicobacter pylori" by Ramis et al 1 . In this study, with a sample size of 57, the authors suggested that cagE is an important prognostic indicator for developing lesions during Helicobacter pylori infection.…”
Section: Dear Editormentioning
confidence: 99%
“…H. pylori CagE has a key role in Cag‐T4SS pilus biogenesis and is essential in H. pylori ‐induced gastritis and peptic ulceration . The cagE gene was recently suggested to represent a risk biomarker for the pathogenicity of H. pylori …”
Section: Introductionmentioning
confidence: 99%
“…Factors related to the host, the diversity of bacterial pathogenicity and the environment seem to be related to the broad clinical spectrum related to infection by H. pylori [31]. Cag E gene is one of virulence factor in the H. pylori organism affecting its pathogenesis potential effect in the gastric mucosa [32]. On the other hand, H. pylori upregulates LL-37/hCAP18 production by the gastric epithelium, suggesting that cathelicidin or its derivative LL-37 contributes to combat chronic infection with this gastric pathogen [22,33].…”
Section: Discussionmentioning
confidence: 99%